Dental microwear textural analysis as an analytical tool to depict individual traits and reconstruct the diet of a primate. Issue 1 (9th October 2017) - Percher, Alice M.; Merceron, Gildas; Nsi Akoue, Gontran; Galbany, Jordi; Romero, Alejandro; Charpentier, Marie JE
Abstract: Objectives: Dental microwear is a promising tool to reconstruct animals' diet because it reflects the interplay between the enamel surface and the food items recently consumed. This study examines the sources of inter‐individual variations in dietary habits in a free‐ranging population of mandrills ( Mandrillus sphinx ) using a combination of feeding monitoring and in vivo dental microwear textural analysis (DMTA). Methods: We investigated the impact of seasonality and individual traits on four DMTA parameters. In parallel, we further studied the influence of the physical properties of the food items consumed on these four parameters, using three proxies (mechanical properties, estimates of phytolith and external grit contents). Results: We found that seasonality, age, and sex all impact DMTA parameters but those results differ depending on the facet analyzed (crushing vs. shearing facets). Three DMTA parameters (anisotropy, complexity, and heterogeneity of complexity) appear sensitive to seasonal variations and anisotropy also differs between the sexes while textural fill volume tends to vary with age. Moreover, the physical properties of the food items consumed vary seasonally and also differ depending on individual sex and age. Conclusion: Considering the interplay between the tested variables and both dental microwear and diet, we reaffirm that food physical properties play a major role in microwear variations. These results suggest that DMTA parameters may provide valuable hints for paleoecological reconstruction using fragmentary fossil dental remains.